INOVASI TEKNOLOGI PAKAN HIJAUAN LOKAL SEBAGAI PAKAN SUPLEMEN DALAM MENINGKATKAN PRODUKSI SUSU KERBAU DI PEMATANG PANJANG KABUPATEN SIJUNJUNG (Jurnal Hilirisasi IPTEKS, 2020)
The Durian Sakek Farmer Group is one of the farmer groups that raised buffaloes whose milk is milked for dadih, located in Nagari Pematang Panjang, Sijunjung Regency, West Sumatera. Buffalo cattle are kept simply released in natural pastures with low feed quality conditions and low milk production. It can be done through improving the quality of feed ingredients. The easiest way to do this is supplementing feeds by utilizing local forage such as cassava leaves with high protein content and widely available in the local area. This activity aims to provide knowledge in technological innovations in the use of local forage feed, especially cassava leaves as a feed supplement for buffalo cattle, so that it can increase buffalo milk production followed by increasing farmer income.The specific target is expected to be to foster community self-help in the utilization of local forage feed as animal feed. The method applied is counselling, training/pilot, discussion, guidance and coaching. The results obtained from this activity increased milk production by 1.05 vs 1.09 l /day and milk quality also increased fat 5.75 vs 7.46%, protein 4.05 vs 5.25%, SNF 10.66 vs 11.45%, Total solid 16.39 vs 19.95 and moisture 83.60 vs 80.05%. The conclusion of this activity is the provision of cassava leaves as supplement feed in the pellets form can increase the production and quality of buffalo milk producing dadih.